EMPATHY GROWN THROUGH KKN PPM UGM TOWARDS UNITY AND COALESCENCE OF PAMULIHAN COMMUNITY - Wiwien Widyawati Rahayu (Lembaga Pengabdian pada Masyarakat, 2014)
Society is a group of people with high dynamic changes. It affects all aspects of life needs to be filled. The difficulty in meeting needs of community life make people easily triggered their anger into committing a crime. The lack of sense in unity and coalescence of communities is caused by the high sense of individualism. KKN with PPM concepts have been done by some Indonesian universities which are emphasized on the process of student dedication to the community. SIPBM is a summary of the data filled by community that has a high accuracy degree of data. The data is the basis for BAPPEDA to solve problems through academic activities. KKN PPM is one form of cooperation between the local goverment through BAPPEDA to seek appropriate solutions to overcome individualism, inability to meet the needs, as well as increased knowledge and skills through community education. KKN PPM program is implemented by the concept of empathy and requires community involvement, either directly or indirectly, at the site to achive unity Pamulihan society through examples of approaches by students. Students involved in KKN PPM are derived from 4 different clusters to solve problems that occur in the community (interdiciplinary). The emergence of service learning program for people receive the program according to the needs, interest, and local characteristics Pamulihan.